Biochemical compositions and fatty acid profiles in four species of microalgae cultivated on household sewage and agro-industrial residues. (December 2016) - Calixto, Clediana Dantas; da Silva Santana, Jordana Kaline; de Lira, Evandro Bernardo; Sassi, Patrícia Giulianna Petraglia; Rosenhaim, Raul; da Costa Sassi, Cristiane Francisca; da Conceição, Marta Maria; Sassi, Roberto
Highlights: The growth of four regional microalgae was evaluated in five residual media. Variations in yield and biomass composition were analyzed in different ways. The MDS and HB media showed promising results for microalgae cultivation. High levels of esters were obtained from biomass grown in HB. Abstract: The potential of four regional microalgae species was evaluated in relation to their cell growth and biomass production when cultured in the following alternative media: bio-composts of fruit/horticultural wastes (HB), sugarcane waste and vinasse (VB) chicken excrements (BCE), raw chicken manure (RCM), and municipal domestic sewage (MDS). The cultures were maintained under controlled conditions and their growth responses, productivities, biochemical compositions, and the ester profiles of their biomasses were compared to the results obtained in the synthetic media. The MDS and HB media demonstrated promising results for cultivation, especially of Chlorella sp., Chlamydomonas sp., and Lagerheimia longiseta, which demonstrated productivities superior to those seen when grown on the control media. The highest lipid levels were obtained with the HB medium. The data obtained demonstrated the viability of cultivating microalgae and producing biomass in alternative media prepared from MDS and HB effluents to produce biodiesel.